Romanticism as political critique: authority, sympathy, and the modern state - Harrison, Rory, author; Steinway, Elizabeth, adviosr; Lessor, Edward, committee member (Colorado State University. Libraries, 2025)
This thesis examines British Romanticism as a sustained political critique of authority, freedom, and systemic power, challenging the longstanding view that Romantic writers retreated from politics after early revolutionary enthusiasm. Drawing on recent scholarship that reframes Romanticism as deeply entangled with war, empire, slavery, ecology, and economic instability, the project argues that Romantic literature persistently interrogates the moral and psychological foundations of political authority. Through close readings of writers including William Wordsworth, William Blake, Percy Bysshe Shelley, Lord Byron, Mary Wollstonecraft, Germaine de Staël, Anna Laetitia Barbauld, and Felicia Hemans, the thesis traces how Romanticism conceptualizes freedom not as a fixed achievement but as an ongoing ethical and imaginative practice. Romantic critiques of revolution, nationalism, humanitarianism, institutional power, and environmental degradation reveal enduring patterns of domination, complicity, and resistance. By extending these insights beyond historical reconstruction, the thesis demonstrates how Romantic political thought illuminates contemporary democratic crises in the United States, including racial inequality, economic precarity, ecological collapse, and the erosion of civic trust. Ultimately, the project argues that Romanticism remains politically vital because it exposes how authority operates both externally through institutions and internally through perception, habit, and imagination, insisting that political renewal begins with moral and imaginative transformation.
English Department.
Keywords: British Romanticism; authority; freedom; political critique; tyranny